TOURISM PERCEPTION OF TURKESTAN RESIDENTS AND THEIR ATTITUDES TOWARDS TOURISM (Journal of Economic Research & Business Administration, 2017)
In this study it has been aimed to determine the tourism perception of residents and what should be done to develop tourism in Turkestan. A questionnaire prepared for this purpose was conducted to residents by the method of simple random sampling. According to questionnaire results obtained from 940 people, it is found that residents in Turkestan define tourism as an activity which provides economic development and they define tourist as person who brings currency. Respondents intensely indicate that in Turkestan existing facilities should be enhanced and service quality should be increased. Moreover, as a result of the analysis of the obtained data, seven factors related to residents’ tourism perception and their attitudes towards tourism have been identified. When the average of these factors in terms of education, monthly income and nationality of residents was taken into account, significant differences have been found.